Delayed Sleep-Wake Phase Disorder: Can Polysomnography Be Useful - Příhodová, Iva; Dostálová, Simona; Bielicki, Petr; Skibová, Jelena; Nevšímalová, Soňa; Šonka, Karel (Pediatric neurology, 2022)
BACKGROUND: Delayed sleep-wake phase disorder (DSWPD) is a chronic condition with a multifactorial etiology that primarily affects adolescents, significantly influencing their quality of life. In clinical practice, the contribution of intrinsic and behavioral factors is difficult to determine. The aim of our study was to compare data from clinical interviews, sleep diaries, actigraphy, and nocturnal polysomnography (PSG) in a cohort of adolescents with DSWPD and to assess psychiatric/neurodevelopmental comorbidity. METHODS: Thirty-one patients (22 male; mean age 15.4 ± 2.2 years, range 12 to 19 years) with a diagnosis of DSWPD based on detailed history, sleep diary, and actigraphy underwent nocturnal polysomnography (PSG) and neurological, psychological, and psychiatric examination. RESULTS: Attention-deficit/hyperactivity disorder (ADHD) was present in 14 cases (45%), specific learning difficulties in nine (29%), and mood disorder (anxiety/depression) in 16 patients (52%). PSG revealed sleep-onset delay in only 12 (38%) cases. No differences in clinical data or psychiatric comorbidity between the group with sleep delay and the group with normal sleep onset were detected. Decreased total sleep time, sleep efficiency, rapid eye movement (REM) sleep, and prolonged REM sleep latency were observed in patients with delayed sleep onset. CONCLUSIONS: PSG showed delayed sleep timing in only 38% of patients with a diagnosis of DSWPD based on diagnostic criteria of the International Classification of Sleep Disorders. We suggest that PSG can provide useful information regarding the prevailing etiology (biological versus behavioral) if dim light melatonin onset testing is not available.
Keywords: mladý dospělý; depresivní poruchy; Child; Comorbidity; Humans; lidé; Sleep Stages; Polysomnography; mladiství; komorbidita; Depressive Disorder; aktigrafie; Specific Learning Disorder; Anxiety Disorders; poruchy spánku a bdění; Female; Male; Adult; Attention Deficit Disorder with Hyperactivity; Sleep Wake Disorders; Mental Disorders; duševní poruchy; mužské pohlaví; Cohort Studies; stadia spánku; ženské pohlaví; polysomnografie; Young Adult; Actigraphy; dospělí; kohortové studie; hyperkinetická porucha; dítě; úzkostné poruchy; Adolescent; specifické poruchy učení